2002
DOI: 10.1023/a:1015847019904
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Elimination of platelets from guinea pig splenocyte suspension (lacking megakaryocytes) with EDTA considerable reduces the efficiency cloning of splenic stromal precursor cells. It means that platelet-derived growth factors are necessary for stromal precursor cells from different organs (bone marrow, thymus, and spleen). The dependence on the platelet growth factors can vary within a wide range in descendants from cultured bone marrow precursor cells (passaged bone marrow fibroblasts at different stages of dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Indeed, addition bone marrow feeder to guinea pig bone marrow stromal fibroblast cultures, where cell differentiation was suppressed by passing the cultures before attaining confluence, did not increase ECF-F. The presence of the feeder in the culture of fibroblasts passed after attaining the confluence and grown in the presence of dexamethasone and L-ascorbate (inductors of osteogenic differentiation of these cells [10]) sharply increased ECF-F and the number of stromal fibroblasts in cultures [3]. However, the route of culturing of passaged rabbit bone marrow fibroblasts did not modulate the dependence of their proliferation on feeder GF ( Table 2).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Indeed, addition bone marrow feeder to guinea pig bone marrow stromal fibroblast cultures, where cell differentiation was suppressed by passing the cultures before attaining confluence, did not increase ECF-F. The presence of the feeder in the culture of fibroblasts passed after attaining the confluence and grown in the presence of dexamethasone and L-ascorbate (inductors of osteogenic differentiation of these cells [10]) sharply increased ECF-F and the number of stromal fibroblasts in cultures [3]. However, the route of culturing of passaged rabbit bone marrow fibroblasts did not modulate the dependence of their proliferation on feeder GF ( Table 2).…”
Section: Resultsmentioning
confidence: 96%
“…It was found that only 25% colonies formed both the bone marrow and bone, some colonies formed only the bone tissue without bone marrow, while others formed only reticular tissue [6]. The dependence of guinea pig bone marrow fibroblasts on GF produced by bone marrow feeder considerably varies at different stages of their differentiation [3]. Indeed, addition bone marrow feeder to guinea pig bone marrow stromal fibroblast cultures, where cell differentiation was suppressed by passing the cultures before attaining confluence, did not increase ECF-F.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation